Dental implant primary stability in different regions of the Jawbone: CBCT-based 3D finite element analysis - Razan Alaqeely; Nadir Babay; Montaser AlQutub (Elsevier, 2020)
Aim: This study aimed to analyze the primary stability of dental implant in maxillary and mandibular anterior and posterior regions using a finite element analysis. Materials and methods: CBCT images of maxillary and mandibular regions were collected from patients' radiographic data and transformed to 3D models. A Straumann Dental implant was inserted in each bone model and then pulled-out, where amount von-Mises stress was obtained and analyzed for each. A comparison between the insertion and the pull-out was evaluated. Results: Twenty-four images were randomly selected for analysis from 122 scans. In both the insertion and the pull-out of the dental implant, von-Mises stress was high in cortical as compared to the cancellous bone (p < 0.0001). Maxillary posterior region had a low von-Mises stress (p < 0.001). Bone plastic deformation was higher in cancellous than the cortical bone in all bone regions and was the lowest in maxillary posterior region (p < 0.001). Bone displacement decreased from Type I to type IV bone. Conclusion: Evaluation of von-Mises stress showed different measurements in maxillary and mandibular regions. Bone deformation was low in the maxillary posterior region.